Co‐Design of the Structured Personalised Assessment for Reviews After Cancer (SPARC) Intervention - Rosalind Adam; Lisa Duncan; Sara MacLennan; Louise Locock; Anne E. Kiltie; Leslie Samuel; Peter Murchie (Health Expectations)
ABSTRACT Introduction An increasing number of people are living beyond cancer with unmet health needs. The aim of this study was to co‐design a digital intervention to improve health outcomes for people who have completed potentially curative treatment for cancer. Methods Two co‐design workshops were held with patients, clinicians (including oncologists, general practitioners and nurses), digital/computing science experts and third‐sector representatives. At workshop one, problems and gaps in care were identified and intervention ideas were generated. At workshop two, a prototype intervention was discussed and refined. Results The workshops were attended by 43 people in total: 26 at event one and 23 at event two (six attended both events). Patients valued relationship‐based care and felt supported during hospital treatment. Patients ‘fell off a cliff’ after discharge, and there was consensus that more could be done in primary care to support those living beyond cancer. It was proposed that cancer reviews could be integrated into UK primary care chronic disease management activities. A digital form, the ‘Structured Personalised Assessment for Reviews after Cancer’ (SPARC) tool, was developed to support asynchronous consultations that would cover the breadth of problems and health promotion activities required for high‐quality primary care for cancer. SPARC could also identify those without problems who do not require review. Conclusion SPARC has been co‐designed to support brief but comprehensive cancer review consultations between primary care clinicians and their patients. SPARC aligns with best practice guidelines. The next step is to evaluate SPARC with patients and in general practices. Patient and Public Contribution Patient and stakeholder engagement was at the centre of this research study. Cancer organisations such as ‘CLAN’ cancer support, Prostate Cancer Scotland and Cancer Research UK helped us to engage with patients. The Aberdeen University Institute of Applied Health Science Patient Public Involvement group were also instrumental in sense‐checking and improving the materials for the second workshop. We plan to involve our patient and carer partners in designing the next stages of our research (including study materials, processes and methods) so that they will be at the centre of evaluating the intervention that they have been instrumental in designing.